Boron phosphide (BP) graphenylene as work function-type sensor for glucose detection: First-principles investigations - Abdullahi, Yusuf Zuntu; Ahmad, Sohail; Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP] (Elsevier, 2025)
Diabetes is a chronic metabolic disorder characterized by elevated blood sugar levels, leading to severe health complications. Non-invasive glucose monitoring is essential for effective diabetes management, and porous materials are promising candidates for this purpose due to their high surface-to-volume ratio and the availability of active sites for adsorption. In this study, we explore the potential of g-BP (graphenylene-like boron phosphide) as a non-enzymatic glucose sensor. Adsorption energies (Eads) for glucose, fructose, and xylose on gaseous (aqueous) media were calculated as −0.74 eV (−1.13 eV), −0.66 eV (−1.04 eV), and −0.58 eV (−1.07 eV), respectively, with the sugar molecules chemisorbed on the g-BP surface. The variations on Eads when water molecules are present are due to hydrogen bonding interactions between H2O and the sugars. Recovery time results indicate that the g-BP monolayer can be utilized as a reusable sensor for these sugar molecules with high selectivity. A band gap opening of approximately 0.67 eV is observed under the adsorption of all sugar molecules. Notably, the work function (ϕ) of g-BP changes significantly upon glucose adsorption for both gaseous and aqueous environments, making it highly sensitive for glucose detection. These findings suggest that g-BP is a promising material for non-invasive work function glucose sensors, as well as for diabetes management.
Keywords: 2D materials; Boron Phosphide; Diabetes; Graphenylene; Sugar detection